Evaluation of hearing in patients of chronic renal failure - Mukhtar, Sabreena; Thomas, James; Ghate, Girija; Khan, Raphella (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic kidney disease (CKD) is considered to be a major public health problem and only some studies have subsequently suggested the possibility of a link between the ear and the kidney. The aim of the study was to look for an association between the hearing loss and its association with CKD in absence of any underlying co-morbidities. Methods: The study design was a hospital based cross sectional study. 50 patients diagnosed with CKD were included. The patients were subjected to general physical examination, examination of ear by otoscopy and hearing test by tuning fork test (256 Hz, 512 Hz and 1024 Hz). Pure tone audiometry (PTA) was also done. Results: It was observed that 24% patients were having unilateral or bilateral hearing loss. Of the 12 patients with hearing loss, PTA threshold was below or equal to 35 dB in 4 patients. Hearing threshold of 45 dB was observed in 3 patients. All 3 patients had unilateral involvement. 2 had hearing loss in right ear whereas left ear was involved in 1 patient. 5 patients had hearing threshold between 45-60 dB. Of these 5 patients, 3 had bilateral ear involvement whereas unilateral ear involvement was seen in remaining 2 patients. Conclusions: CKD is commonly associated with senorineuronal hearing loss. The incidence was 24% in our study population. PTA can be a non-invasive procedure which may be employed to detect CKD patients suffering from any hearing loss.